2013
DOI: 10.4103/0300-1652.126290
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of radiation protection practices among radiographers in Lagos, Nigeria

Abstract: Background:Use of ionising radiation in diagnostic radiography could lead to hazards such as somatic and genetic damages. Compliance to safe work and radiation protection practices could mitigate such risks. The aim of the study was to assess the knowledge and radiation protection practices among radiographers in Lagos, Nigeria.Materials and Methods:The study was a prospective cross sectional survey. Convenience sampling technique was used to select four x-ray diagnostic centres in four tertiary hospitals in L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 9 publications
2
22
1
Order By: Relevance
“…Bicornuate uterus was also found to be commonest congenital uterine anomaly by Bukar M et al [19] (1.8%) and Aziz MU et al [20] (4.0%), whereas unicornuate uterus was commonest in study of Shrivastava VR et al [7] (1.6%) with bicornuate uterus seen in 1.2%. Uterine fibroid (16.9%) was as well seen to be commonest acquired uterine abnormality in study of Eze CU et al [31] (synechiae 5.3%), in contrast to the finding of Bukar M et al [19] who reported synechiae (12.9%) to be common than fibroid (5.9%). As this study was based on single center, results may not represent entire population.…”
Section: Resultscontrasting
confidence: 53%
“…Bicornuate uterus was also found to be commonest congenital uterine anomaly by Bukar M et al [19] (1.8%) and Aziz MU et al [20] (4.0%), whereas unicornuate uterus was commonest in study of Shrivastava VR et al [7] (1.6%) with bicornuate uterus seen in 1.2%. Uterine fibroid (16.9%) was as well seen to be commonest acquired uterine abnormality in study of Eze CU et al [31] (synechiae 5.3%), in contrast to the finding of Bukar M et al [19] who reported synechiae (12.9%) to be common than fibroid (5.9%). As this study was based on single center, results may not represent entire population.…”
Section: Resultscontrasting
confidence: 53%
“…Once the optimal parameters are defined and included in written procedures, local radiographers and radiologists have to make sure that they are properly applied. Indeed, discrepancies between adherence to radioprotection policies and knowledge in radiation protection may occur [3]. As this decision-making process is operatordependent, and as variations are deleterious for quality, it seemed justified to control the proper use of these procedures [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Abubakar et al (2016) [8], assessed the ambient radiation doses at FMC Asaba, Nigeria. Eze et al (2013) [9], and Usen and Umoh (2014) [10], assessed radiation protection practices among radiographers in Lagos (western), and Maiduguri (northern) Nigeria, respectively. The evaluation of x-ray effects on haematological parameters of radiographers was beyond the scopes of these studies.…”
Section: Introductionmentioning
confidence: 99%